Field-based physical performance of elite and sub-elite middle-adolescent soccer players - Trecroci, A.; Longo, S.; Perri, E.; Iaia, F. M.; Alberti, G. (Research in Sports Medicine, 2019)
The aim of the current study was to evaluate field-based physical performance of under 16 years (U16) elite and sub-elite soccer players. Forty elite (n = 20) and sub-elite (n = 20) soccer players were enrolled and tested for countermovement jump (CMJ), 10-m sprint and agility, in terms of sprint with 90° turns (S90), S90 with ball, Slalom, Slalom with ball, and reactive agility (RAT). Statistical and practical significant differences were observed in CMJ, S90 and RAT between elite and sub-elite. Elite players exhibited a likely better performance in Slalom, Slalom with ball and S90 with ball despite a non-significant difference by level of play. Concerning sprint ability, both groups showed similar performance in the 10-m sprint. Countermovement jump and agility tests are field-based physical assessments recommended to better distinguish between U16 elite and sub-elite soccer players.